The quarry [videorecording (DVD)] - Teems, Scott; Teems, Scott; Bichir, Bruno; Whigham, Shea, 1969-; Watt, Anna; Galgut, Damon, 1963- (Lionsgate, 2020)
A drifter arrives in a small town impersonating a traveling preacher he killed and arouses the suspicion of the police chief.